Demonstration of protein capture and separation using three‐dimensional printed anion exchange monoliths fabricated in one‐step. Issue 6 (26th October 2020) - Simon, Ursula; Scorza, Livia C T; Teworte, Sarah; McCormick, Alistair J; Dimartino, Simone
Abstract: Three‐dimensional printing applications in separation science are currently limited by the lack of materials compatible with chromatographic operations and three‐dimensional printing technologies. In this work, we propose a new material for Digital Light Processing printing to fabricate functional ion exchange monoliths in a single step. Through copolymerization of the bifunctional monomer [2‐(acryloyloxy)ethyl] trimethylammonium chloride, monolithic structures with quaternary amine ligands were fabricated. The novel formulation was optimized in terms of protein binding and recovery, microporous structure, and its swelling susceptibility by increasing its cross‐link density and employing cyclohexanol and dodecanol as pore forming agents. In static conditions, the material demonstrated a maximum binding capacity of 104.2 ± 10.6 mg/mL for bovine serum albumin, in line with commercially available materials. Its anion exchange behavior was validated by separating bovine serum albumin and myoglobin on a monolithic bed with Schoen gyroid morphology. The same column geometry was tested for the purification of C‐phycocyanin from clarified as well as cell‐laden Arthrospira platensis feedstocks. This represents the first demonstration of one‐step printed stationary phases to capture proteins directly from solid‐laden feedstocks. We believe that the material presented here represents a significant improvement towards implementation of three‐dimensional printed chromatography media in the field of separation science.